The effect of exchange rate fluctuations on the performance of small and medium sized enterprises: Implications for Brexit - Belghitar, Yacine; Clark, Ephraim; Dropsy, Vincent; Mefteh-Wali, Salma (Elsevier, 2021)
This paper develops an innovative technique that takes into account the time varying nature of exchange rate (XR) exposures and separates these exposures into those that increase stock market returns and those that reduce them to study the effect of XR fluctuations on the performance of UK small and medium sized enterprises (SMEs). It provides evidence that XR fluctuations have a strong negative effect on SME performance at the industry and individual firm level for both depreciations and appreciations of the GBP against the USD and a residual index of all other currencies except the euro. For the euro, the exposures are much smaller at the industry level and generally not statistically significant. At the firm level they are also more evenly divided between performance enhancing and performance decreasing. Differences of exposures to currency variations between export-oriented firms and domestically-focused firms are also analyzed. Our results have policy implications for Brexit.
Keywords: good/bad exposures; Asymmetric exchange rate exposure; Share price performance; SME